The Effect of Brand Image and Product Quality on Buying Interest in Specs Futsal Shoes - Rhamadhony, Prayoga; Gayatri, Ida Ayu Made Er Meytha; Rahman, Abdul (Journal of Law, Social Science, and Management Review, 2024)
Brand image is a guideline that consumers use to judge a product when they do not have enough knowledge about a product. Product quality is the core of a marketing activity because the product is the output or result of one of the company's activities or activities that can be offered to the target market to meet the needs and desires of consumers and buying interest is a type of consumer behavior that occurs as a response to an object that shows the consumer's desire to buy something. This thesis is entitled The Influence of Brand Image and Product Quality on the Interest in Buying Futsal Specs Shoes at the Queen Style Shop in South Bengkulu. The purpose of this study is to determine the influence of brand image and quality in the face of buying futsal shoes Specs. This study uses a qualitative research method, the sample that was researched in this study amounted to 98 peopel and sample sampling using the incidental sampling mothod. Based on the multiple linear results, the regression equation Y=0.233+0.029X1+0.0652X2 was obtained. The results of the research showed that the value of R²=0.982 The results of the study and hypothesis showed that citra merek (X1) had a significant increase in buying interest, namely t calculate t tables (0.504>0.167)and(sig a+0.001 ltables (0.651>0.05) and (sig a=0.001 ftables (12.149>0.167) and (sig a = 0.001 < 0.050).